(untitled) (Journal of Universal Science Research, 2024)
This article explores the therapeutic benefits and historical significance of salt mines as unique healing places. From ancient civilizations to modern wellness seekers, salt mines have been revered for their ability to promote respiratory health, relaxation, and overall well-being. Through halotherapy and immersive experiences, visitors to salt mines can escape the stresses of modern life and reconnect with themselves in the serene ambiance of the underground environment.